Students’ Influences of CAA: A Case Study of Senior High School in Badung Bali - Putri, I Gusti Ayu Vina Widiadnya (Universitas Malikussaleh, 2019)
The aims of this study is to find out and analyzed about students’ influences of Computer-assisted assessment (CAA) It is the case study and field research of one school in Nusa Dua Badung-Bali. The data sources chosen in this study were several high schools that carried out online examinations at Nusa Dua Vocational high school Bali-Indonesia. Data collection is done by random sampling from data sources, observation, interviews, recording, and note taking. Distribution of questionnaires was also carried out to strengthen data analysis. Data is analyzed based on the formulation of the problem and the study of theory that has been, then analyzed in qualitative description. The descriptive study used paper-based surveys and interviews for data collection. To obtain information about the students’ influences of Computer-assisted assessment (CAA). Based on our review and study result, there are some influences that found. The Computer-assisted assessment (CAA) systematics is held with the aim that students become more critical and independent in solving the questions given.